Transformation of Sustainability Science Education: PISA 2025 Science Framework and ESD on E-Worksheets Science in the Context of the Role of Peatland in Global Warming Phenomenon - Kurdiati, Lintang Auliya; Apriana, Rosalina; Saparini, Saparini (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
Global warming remains a critical global challenge that affects multiple dimensions of life and demands immediate, coordinated action. Peatlands, which have a dual capacity to either mitigate or exacerbate global warming, are increasingly subject to degradation. Addressing this issue requires a transformative approach to science education, emphasizing sustainability. This transformation can be achieved through the development of e-worksheets that integrate the PISA 2025 Science Framework and Education for Sustainable Development (ESD). This study aims to design e-worksheets for science education that incorporate these frameworks, with a focus on elucidating the role of peatlands in the global warming phenomenon. The research adopts a development research methodology based on the Rowntree model, involving 12 tenth-grade students from a state high school in South Sumatra during the 2023/2024 academic year as participants in the product evaluation phase. The evaluation method is driven by Tessmer's formative evaluation paradigm, which includes self-evaluation, expert review, one-to-one evaluation, and small group evaluation. Interviews, walkthroughs, and questionnaires are among the data collection methods used. The analysis results show that the expert review phase produced an average validation score of 94.2%, which is classified as extremely valid. Furthermore, the one-to-one and small group evaluation stages yielded average practicality values of 86.25% and 97.5%, respectively, classifying them as extremely practical. These findings suggest that the produced e-worksheets, which are geared toward the PISA 2025 Science Framework and ESD, are both valid and practicable for classroom use, particularly in terms of improving students' understanding of the essential role of peatlands in the global warming catastrophe.